Measuring Resilience of Urban Slum to Climate Induced Disasters: A Study on Barishal City Corporation, Bangladesh - Ananya Mukherjee; Md. Faisal; Milton Kumar Saha (TDMRC, Universitas Syiah Kuala, 2020)
Measuring urban resilience is one of the important processes toward understanding the potential current and future risks of cities, assessing the challenges of urbanization and to guide the development of urban areas. The research was conducted in a slum named Bangabandhu Colony under Barishal City Corporation (BCC). The purpose of the research was to measure the urban disaster resilience and to find out a better way of future urban disaster resilience in this area. Climate Disaster Resilience Index (CDRI) was used to measure climate-related disaster resilience by considering five dimensions: physical, social, institutional, economic and natural which shows resilience level ranging from 1-5 where 1 representing very poor and 5 best. A semi-structured questionnaire was used for collecting the primary data and the secondary data was collected from secondary sources. Results revealed that the resilience level of physical, social, institutional, economic, and natural dimensions was 2.76, 2.79, 2.29, 2.53, 2.59 respectively, which indicates a medium resilience level of all dimensions. Finally, the research depicted that, the resilience level of the area will increase through hand to hand working of people with government and non-government officials, conducting public awareness programs, campaigns, seminars and discussions. The findings of the research can be used by researchers and development workers for enhancing disaster resilience of other areas under Barishal City Corporation as well as other city areas of Bangladesh.